A new antiferromagnetic Dy6 oxido-material as a multifunctional aqueous phase sensor for picric acid as well as Fe3+ ions. Issue 9 (25th November 2020) - Raizada, Mukul; Shahid, M.; Hussain, Sameer; Ashafaq, Mo; Siddiqi, Zafar A.
Abstract : A new Dy6 -oxo based multisensory material for picric acid and ferric cations in aqueous medium is developed and characterized. Abstract : Owing to the continuous significance of high nuclearity clusters as sensory materials, an attempt is made to develop a new octahedron like Dy6 cluster as a promising agent to detect picric acid (PA) and Fe 3+ in the aqueous phase. A novel oxido-metal (OM)-based inorganic compound was synthesized using a green approach. Single crystal X-ray data ascertained the bonding modes and geometry composition of the cluster [Dy6 (μ6 -O)(μ3 -OH)8 (H2 O)12 (NO3 )6 ](NO3 )2 (H2 O)2 (1 ) containing a distorted octahedral oxido ion (O 2− ) at the center of the hexanuclear cage. The complex was further characterized by spectral and magnetic studies. The variable temperature magnetic susceptibility data indicate an antiferromagnetic interaction existing between Dy III ⋯Dy III ions with Curie constant 79.55 cm 3 K mol −1 and Weiss constant −7.65 K. The cluster displayed intermolecular O–H⋯O and O–N⋯O interactions forming a supramolecular framework. These interactions have been verified by Hirshfeld surface analyses. The Ln discrete material is disclosed as the first aqueous phase dual sensor for picric acid (PA) and Fe 3+ . The complex shows highly sensitive, discriminative and selective sensing behavior for the said species. The sensing mechanism is investigated by spectral titration, time decay and DFT (B3LYP/def2-SVP) studies. The detection limit has been discovered for the present OM towards the sensing of PA and Fe 3+ ions to be ∼0.03 and ∼0.09 ppb, respectively, and therefore this becomes the first cage as a dual-sensor for an explosive and a metal ion.